Chemical characteristics and identification of PM10 sources in two districts of Lima, Peru - Ilizarbe-Gonzáles, Gina Mishel (2020)
This study evaluates the concentration of PM10 and PM2.5 andidentifies the sources of pollution in the districts of San Juan de Lurigancho (SJL) and Puente Piedra (PPD) located in the eastern and northern zones of the Metropolitan area of Lima,Peru. The samples were collected between April and May 2017 by the National Meteorology and Hydrology Service of Peru (SENAMHI). The concentrations of PM10 and PM2.5, measured using gravimetric techniques, exceeded the international (WHO) and national reference values; with maximum values for PM10 and PM2.5 of 160 and 121.56 µg/ m3 in PPD and 295.06 and 154.58 µg/ m3 in SJL respectively. Pollution sources were identified using the Positive Matrix Factorization Model (PMF 5.0) and Principal Component Analysis (PCA), and showed similar sources for both districts. In SJL, sources were determined to be a combination of vehicular traffic and the resuspension of soil dust, marine aerosols and iron and steel industry by-products, while in PPD they consisted of the resuspension of soil dust, vehicular traffic, industrial activity and marine aerosols.